Impaired extraction of speech rhythm from temporal modulation patterns in speech in developmental dyslexia - Leong, Victoria; Goswami, Usha (Frontiers in Human Neuroscience, 2014)
Dyslexia is associated with impaired neural representation of the sound structure of words (phonology). The ‘phonological deficit’ in dyslexia may arise in part from impaired speech rhythm perception, thought to depend on neural oscillatory phase-locking to slow amplitude modulation (AM) patterns in the speech envelope. Speech contains AM patterns at multiple temporal rates, and these different AM rates are associated with phonological units of different grain sizes, e.g. related to stress, syllables or phonemes. Here, we assess the ability of adults with dyslexia to use speech AMs to identify rhythm patterns. We study 3 important temporal rates : 'Stress' (~2 Hz), 'Syllable' (~4 Hz) and 'Sub-beat' (reduced syllables, ~14 Hz). 21 dyslexics and 21 controls listened to nursery rhyme sentences that had been tone-vocoded using either single AM rates from the speech envelope (Stress only, Syllable only, Sub-beat only) or pairs of AM rates (Stress+Syllable, Syllable+Sub-beat). They were asked to use the acoustic rhythm of the stimulus to identity the original nursery rhyme sentence. The data showed that dyslexics were significantly poorer at detecting rhythm compared to controls when they had to utilise multi-rate temporal information from pairs of AMs (Stress+Syllable or Syllable+Sub-beat). These data suggest that dyslexia is associated with a reduced ability to utilise AMs < 20 Hz for rhythm recognition. This perceptual deficit in utilising amplitude modulation patterns in speech could be underpinned by less efficient neuronal phase alignment and cross-frequency neuronal oscillatory synchronisation in dyslexia. Dyslexics' perceptual difficulties in capturing the full spectro-temporal complexity of speech over multiple timescales could contribute to the development of impaired phonological representations for words, the cognitive hallmark of dyslexia across languages.